Sensores baseados em redes de Bragg em fibras óticas para análise de movimentos mandibulares e forças de mordida - Nascimento, Paula Fernandes do (2018)
In this work we report the development of a method to characterize mandibular movements and bite force based on Bragg Gratings in optical fibers. The gratings are inserted in to the occlusal splints, usually used to treatment of muscle pain resulting from parafunctional habit and or occlusal alterations. The sensors are positioned in the maxillary first molars regions above the points of contact with opposing teeth. The experiments are realized in vivo by patients with occlusal parafunction and the sensors are used to measure different jaw movements. The characterizations of the force distribution in the splints are realized by using different movements induced by the volunteer. Two different occlusal splints are investigated, resilient and rigid splints, through the obtained results with the sensors. The analysis of muscle fatigue is performed with a patient that wears a resilient occlusal splint. Maximum bite forces are used to induce rapid exhaustion for the analysis of fatigue. In addition, sensors are also used to monitor the force distribution in a volunteer with bruxism that wear a resilient occlusal splint during sleep. The results indicate that the proposed method is a powerful tool for the characterization of occlusal splints and for the investigation of parafunctional problems like fatigue and bruxism.